Rethinking Tourism’s Definition, Scope and Future of Sustainable Work and Employment [Editorial] - Mooney, Shelagh; Robinson, Richard; Solnet, David; Baum, Tom (Taylor & Francis, 2022)
This special issue of the Journal of Sustainable Tourism showcases research that addresses an identified gap that is the relative neglect of the sustainability concept in a workforce context. The special issue presents 10 papers, each making a unique and distinct contribution to knowledge. This extended review/editorial presents a critique of current definitions of sustainability in an employment, and specifically in a tourism employment context, acknowledging and critiquing extant literature. The review then moves on to summarising all the submissions to this special issue, uniquely recognising the themes from both submissions as well as accepted papers. These exercises culminate in the presentation of a refreshed conceptualisation of sustainable employment, before we introduce the final selected papers. The submissions are mapped onto a proposed conceptual framework, which recognises the multi-dimensional influences of the evolving Sustainable Development Goals (SDGs), recent Sustainable Human Resource Management (SHRM) and tourism literature, and the hot-off-the-press contributions to theory of this special issue. Finally, the paper offers concluding remarks that we hope will influence and guide future research endeavours.
Keywords: Sustainable work/employment; Tourism; SDG’s; Sustainable HRM; Gender